Effect of therapeutic sequence of hot pack and ultrasound on physiological response over trigger point of upper trapezius - Dararat Benjaboonyanupap (2018)
© 2015, Sports Medicine Research Center. Background: Musculoskeletal pain is a common problem among athletes. Apart from sport injuries, the myofascial pain syndrome is another important problem that affects performance of the athlete. Objectives: The aim of this study was to evaluate the effects of therapeutic sequences of the hot pack in combination with ultrasound on the physiological responses over the latent myofascial trigger point (LMTrP) of upper trapezius muscle. Materials and Methods: Thirty subjects with a latent myofascial trigger point (LMTrP) in both sides of the upper trapezius muscle participated in the study (age 27.33 ± 4.34 years, weight 58.11 ± 7.47 kg, height 161.50 ± 5.82 cm, pressure pain threshold 2.28 ± 0.24 kg/cm2, pain intensity 7.17 ± 2.25 VAS). All subjects received both treatments (hot pack followed by ultrasound: HP + US; and ultrasound followed by hot pack: US + HP) by randomization with a 24 to 48-hour interval between sessions. Outcome measures, including the tissue blood flow (TBF), pressure pain threshold (PPT), supra-thermal threshold (STT) and visual analog scale (VAS) were evaluated at baseline, immediately, after 30 minutes and after 60 minutes. Results: The TBF and PPT significantly increased from baseline in both treatment conditions (i.e. HP + US and US + HP), while the HP + US condition showed a trend toward significant difference in VAS and STT in 45°C. Conclusions: The application of HP and US treatment induces physiological responses (especially, TBF and PPT) on the LMTrP. This finding provides the direction toward the management of MTrPs condition.